Diversity, inclusion, and the voice of older people: engagement and decision-making in seniors' organizations - Petriwskyj, Andrea (2018)
Seniors$1 (Borganizations play a vital role representing older people in policymaking. The impact of diversity among older people on organizations$1 (Bengagement and decision-making processes therefore has implications for democratic inclusion. Interviews were conducted with paid and voluntary managers of Australian seniors$1 (Borganizations, along with analysis of organizational documents. Findings identified issues of presence and participation and challenges inherent in inclusive deliberation, highlighting the importance of leadership. Leaders$1 (Bunderstandings about what drives and impedes participation, who and what is represented, and how inclusion should be practiced are vital. It is important to consider how organizations can be supported to facilitate inclusion as their constituencies grow. - Reproduced.s